Penggunaan Lembar Analisis Materi Pada Metode Diskusi Presentasi dalam Upaya Peningkatan Efektivitas Pembelajaran - Leni Lustiawati Dewi; Supardi Supardi (PANDITA : Interdisciplinary Journal of Public Affairs, 2023)
The purpose of using the Material Analysis Sheet in the Discussion Method is to improve the learning achievement of each student in learning activities. This analysis sheet is used to measure how far the student is able to absorb and understand the material during the discussion. Improving the effectiveness of learning, what the author wants to know is on two aspects of the assessment, namely the process aspect and the result aspect. The process aspect is explored in two ways, namely the assessment carried out by the teacher and the assessment by the audience. The assessment carried out by the teacher is addressed to all students regarding the learning process. This assessment uses the Process Assessment Sheet. While the audience assessment is aimed at the presenter group, it is carried out using the Material Evaluation Sheet. The results of the assessment of these two methods are combined and divided into two to get the value of learning effectiveness in the process aspect. Meanwhile, the author can explore aspects of the results by looking at the post-test scores by conducting written tests in the form of multiple choice questions (multiple chois), which are carried out at the end of the lesson. Learning is said to be effective, that is, when it reaches the predetermined targets. In the process aspect, the researcher stated that it was effective if the process assessment had achieved a score of 80% or more. Meanwhile, the outcome aspect is declared effective if students who achieve KKM (posttest score = 70) are at least 70% of the total number of students.